Models of palliative care delivery in the United States - Morrison, R. Sean (Curr Opin Support Palliat Care, 2013)
PURPOSE OF REVIEW: To summarize the current United States healthcare system and describe current models of palliative care delivery. RECENT FINDINGS: Palliative care services in the USA have been heavily influenced by the public–private fee-for-service reimbursement system. Hospice provides care for 46% of adults at the end-of-life under the Medicare hospice benefit. Palliative care teams in hospitals have rapidly expanded to provide care for seriously ill patients irrespective of prognosis. To date, over two-thirds of all hospitals and over 85% of mid to large size hospitals report a palliative care team. With the passage of the Patient Protection and Affordable Care Act of 2010, healthcare reform provides an opportunity for new models of care. SUMMARY: Palliative care services are well established within hospitals and hospice. Future work is needed to develop quality metrics, create care models that provide services in the community, and increase the palliative care workforce.